Engaging communities as partners in health crisis response: a realist-informed scoping review for research and policy - Mateus Kambale Sahani; Harro Maat; Dina Balabanova; Mirkuzie Woldie; Paul Richards; PARES Research Group; Susannah Mayhew (BMC, 2024)
Abstract Background Health is increasingly affected by multiple types of crises. Community engagement is recognised as being a critical element in successful crisis response, and a number of conceptual frameworks and global guideline documents have been produced. However, little is known about the usefulness of such documents and whether they contain sufficient information to guide effective community engagement in crisis response. We undertake a scoping review to examine the usefulness of conceptual literature and official guidelines on community engagement in crisis response using a realist-informed analysis [exploring contexts, mechanisms, and outcomes(CMOs)]. Specifically, we assess the extent to which sufficient detail is provided on specific health crisis contexts, the range of mechanisms (actions) that are developed and employed to engage communities in crisis response and the outcomes achieved. We also consider the extent of analysis of interactions between the mechanisms and contexts which can explain whether successful outcomes are achieved or not. Scope and findings We retained 30 documents from a total of 10,780 initially identified. Our analysis found that available evidence on context, mechanism and outcomes on community engagement in crisis response, or some of their elements, was promising, but few documents provided details on all three and even fewer were able to show evidence of the interactions between these categories, thus leaving gaps in understanding how to successfully engage communities in crisis response to secure impactful outcomes. There is evidence that involving community members in all the steps of response increases community resilience and helps to build trust. Consistent communication with the communities in time of crisis is the key for effective responses and helps to improve health indicators by avoiding preventable deaths. Conclusions Our analysis confirms the complexity of successful community engagement and the need for strategies that help to deal with this complexity to achieve good health outcomes. Further primary research is needed to answer questions of how and why specific mechanisms, in particular contexts, can lead to positive outcomes, including what works and what does not work and how to measure these processes.